New occurrence of eclogitic continental rocks in NW Himalaya: The Stak massif in northern Pakistan - Guillot, Stéphane; Riel, Nicolas; Hattori, Kéiko; Desgreniers, Serge; Rolland, Yann; Van Melle, Jérémie; Latif, Mohamad; Kausar, Allah B; Pêcher, Arnaud (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1259 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.57